Schwinger–Dyson equation boundary conditions induced by ETC radiative corrections - Doff, A.; Natale, A. A. [UNESP] (Springer Nature, 2018)
The technicolor (TC) Schwinger–Dyson equations (SDE) should include radiative corrections induced by extended technicolor (ETC) interactions when TC is embedded into a larger theory including also QCD. These radiative corrections couple the different strongly interacting Dyson equations. We discuss how the boundary conditions of the coupled SDE system are modified by these corrections, and verify that the ultraviolet behavior of the self-energies are described by a function that decreases logarithmically with momentum.